PENGARUH INTELLECTUAL CAPITAL TERHADAP COMPANY’S PERFORMANCE DENGAN FIRM’S VALUE SEBAGAI VARIABEL MODERATING PADA INDUSTRI PERBANKAN DI INDONESIA - Farida Tyas Styaningrum; Tri Widyastuti; Darmansyah Darmansyah (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2020)
This study intened to analyze the effect of intellectual capital (value added physical capital value added human capital, value added structutal capital) on company performance and firm value as a moderating variable in banking companies in Indonesia. The independent variable of this study is Intellectual capital, the dependent variable is the company's performance and the moderating variable is firm value. The sample used in this study is the banking institution that reports the composite value of good corporate governance by self assessment in 2012-2016. The sample was conducted using the purposive method sampling. The statistical method uses Partial Least Square. The data used is quantitative data with an empirical study approach for secondary data. The results of the study show that intellectual capital significantly positively influences company performance with firm value as a moderating variable. The limitation of this study is that the observations used in this study are relatively few and cannot explain one decade that is limited to banks listed on the Indonesia Stock Exchange in 2012-2016, this is related to the existence of data limitations.